Science and development of muscle hypertrophy - Schoenfeld, Brad 1962- (Human Kinetics, 2021)
"Science and Development of Muscle Hypertrophy, Second Edition, is a compilation of science-based principles to help professionals develop muscle hypertrophy in athletes and clients. It highlights the aspects of muscle hypertrophy that are currently being examined, and it tells readers how to apply the research conclusions for maximal hypertrophic development"--Provided by publisher.